2021
DOI: 10.7717/peerj.10864
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of genes related to cold tolerance in Dendroctonus valens

Abstract: Pine beetles are well known in North America for their widespread devastation of pine forests. However, Dendroctonus valens LeConte is an important invasive forest pest in China also. Adults and larvae of this bark beetle mainly winter at the trunks and roots of Pinus tabuliformis and Pinus sylvestris; larvae, in particular, result in pine weakness or even death. Since the species was introduced from the United States to Shanxi in 1998, its distribution has spread northward. In 2017, it invaded a large area at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…First, only the adults were exposed to extended cold exposure (2–20 days) prior to tissue collection. Importantly, cold exposure can induce changes in gene expression in insects (see Freda et al, 2017; Zhao et al, 2021 and references therein). We note, however, that the 4℃ storage that we used was more moderate than most experiments (typically 0℃) that have investigated the impact of cold stress or chill‐comas on gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, only the adults were exposed to extended cold exposure (2–20 days) prior to tissue collection. Importantly, cold exposure can induce changes in gene expression in insects (see Freda et al, 2017; Zhao et al, 2021 and references therein). We note, however, that the 4℃ storage that we used was more moderate than most experiments (typically 0℃) that have investigated the impact of cold stress or chill‐comas on gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, N. lecontei adults recover from the 4℃ chill-coma within minutes and immediately resume normal mating and host-seeking behaviours. Although adults are likely to encounter low temperatures in the field, it is nevertheless possible that cold storage could contribute to differences in gene expression between adults and larvae (Freda et al, 2017;Pujol-Lereis et al, 2014;Zhao et al, 2021). To reduce this effect, we warmed adults to room temperature (22℃) and enclosed them in a mesh cage containing Pinus seedlings for a minimum of 15 min to ensure that they exhibited normal host-and mate-seeking behaviour.…”
Section: Tissue Dissection In Laboratory-reared N Leconteimentioning
confidence: 99%
“…Transcriptome sequencing technology plays a vital role in non-model insect gene discovery and gene function studies. The technology has enabled various species ( Bayega et al, 2021 ; Zhan et al, 2021 ; Zhao et al, 2021 ). We performed transcriptome and RNA-SEQ sequencing on the T. papillosa genome at different developmental stages and different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In September, RTBs overwinter as mature larvae, adults, even pupae, 2nd-or 3rd-instar larvae [16]. In recent years, alongside the distribution of pine forest, RTB has spread to more northern regions of China, such as Liaoning province and the Inner Mongolia Autonomous Region [17][18][19]. Due to the severity of the RTB outbreak in China, various aspects of the invasion dynamics of this insect have been studied [14], including its ecology [20] and yeast associates [15], the bioactivities of microorganisms against host defensive monoterpenes [21], the survival of RTB and its adaptability to a climate warming scenario [22], and the diversity of fungi associated with the insect [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that glycerol, trehalose, and sorbitol may help RTB larvae to survive during overwintering [29]. Recently, Zhao et al [19] compared the transcriptomes of wintering and non-wintering adult and larval D. valens, then identified a series of genes associated with cold tolerance. Another factor limiting the supercooling ability of insects is the existing of nucleating agents catalyzing ice formation at high subzero temperatures [30].…”
Section: Introductionmentioning
confidence: 99%